Gender Digital Divide in Migratory Contexts: The Case of Peruvian Migrant Women in Italy and Spain - Ortiz Cobo, Mónica; Jeri Levano , Renzo Ismaél (Journal of Education Culture and Society, 2023)
Aim. This ethnographic study explores the impact of the digital divide within the collective of Peruvian migrant women employed in a highly precarious sector, such as domestic services.Methods. This has become evident in this multisite and virtual ethnography, with the following objectives: to analyse the variables that affect digital exclusion, in addition to identifying and deepening the different digital competencies and uses of Information and communication technologies (ICT) in the migratory projects of Peruvian migrant women. In order to achieve these objectives, we undertook fieldwork during the COVID-19 pandemic in two contexts, Italy and Spain, using semi-structured interviews and virtual observation, during which we employed online social networks as research tools.Results. Although digital inequality was a reality prior to COVID-19, it has been worsened by the pandemic, at which time we began our fieldwork. Inequalities between men and women in the different areas of society are reproduced within the context of new technologies. This is termed the gender digital divide and is considered a form of social exclusion, which intensifies and feeds back into itself. Gender inequality in terms of the use of ICT and digital skills intensifies in communities that are even more vulnerable, such as migrant women, whose plenary incorporation into information society is limited.Conclusion. The use of ICT can aid in social inclusion of migrants in digitally advanced societies. However, Peruvian migrant women face new forms of social exclusion due to limited digital access, economic difficulties, and individual digital skills, leading to a gender and generational digital gap.